The mummies of San Lorenzo Island - Guido P. Lombardi; Uriel García-Cáceres (Journal of Biological Research, 2021)
San Lorenzo Island is 5 miles off the coast of Lima, Peru. This island, as well as the whole Peruvian coast, presents several environmental conditions that make natural mummification a very common phenomenon. This paper explains the reasons for this phenomenon and presents an overview of the bodies recently uncovered by a team of archeologists led by the Peruvian Navy.